2008
DOI: 10.1007/s00125-008-0987-y
|View full text |Cite
|
Sign up to set email alerts
|

The Neuropad test: a visual indicator test for human diabetic neuropathy

Abstract: Aims/hypothesis The commercially available Neuropad test was developed as a simple visual indicator test to evaluate diabetic neuropathy. It uses a colour change to define the integrity of skin sympathetic cholinergic innervation. We compared the results of Neuropad assessment in the foot with established measures of somatic and autonomic neuropathy. Methods Fifty-seven diabetic patients underwent Neuropad assessment, quantitative sensory and autonomic function testing, and evaluation of intra-epidermal nerve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
88
5
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(105 citation statements)
references
References 31 publications
(29 reference statements)
11
88
5
1
Order By: Relevance
“…The present study applied this instrument to evaluate DPN and found that the mTCNS was significantly higher in patients with an abnormal and a patchy Neuropad response in comparison to those with a normal response. The time to complete the color change has been reported to be significantly associated with the clinical staging of DPN (8,16) diagnosed through NDS, showing that patients with time to change between 600 and 1,000 s, which may correspond to the patchy Neuropad responders in the current study, could have mild or moderate DPN diagnosed through the NDS. Likewise, patients with a time to color change between 1,000 and 1,200 s have moderate DNP and those scoring >1,200 s appear to have severe DNP.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The present study applied this instrument to evaluate DPN and found that the mTCNS was significantly higher in patients with an abnormal and a patchy Neuropad response in comparison to those with a normal response. The time to complete the color change has been reported to be significantly associated with the clinical staging of DPN (8,16) diagnosed through NDS, showing that patients with time to change between 600 and 1,000 s, which may correspond to the patchy Neuropad responders in the current study, could have mild or moderate DPN diagnosed through the NDS. Likewise, patients with a time to color change between 1,000 and 1,200 s have moderate DNP and those scoring >1,200 s appear to have severe DNP.…”
Section: Discussionmentioning
confidence: 55%
“…Diabetic autonomic dysfunction has been principally evaluated centrally by assessing heart rate variability (4), and peripherally by assessing sweating using complex and expensive equipment (5). A new Neuropad test (6)(7)(8) for sudomotor function has been developed as a simple visual indicator test to evaluate DPN. On the other hand, several instruments (9,10) have developed for use in clinical practice because clinical evaluation of DPN is complex.…”
Section: Introductionmentioning
confidence: 99%
“…It was also shown that CCM correlate with the intraepidermal nerve fiber (IENF) loss in skin biopsies from the dorsum of the foot in diabetic patients [12] and may also show nerve repair after pancreas transplantation [24].…”
Section: Discussionmentioning
confidence: 99%
“…Only biopsy of the sural nerve and skin biopsy allows a direct examination of nerve fiber damage and repair [11]. However, both are invasive procedures, and assessment of therapeutic efficacy in clinical trials requires repeated biopsies [12].…”
Section: Background and Aimsmentioning
confidence: 99%
See 1 more Smart Citation